2014
DOI: 10.3390/ijerph110909361
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of the Impact of a Stand-Biased Desk on Energy Expenditure and Physical Activity for Elementary School Students

Abstract: Due to the increasing prevalence of childhood obesity, the association between classroom furniture and energy expenditure as well as physical activity was examined using a standing-desk intervention in three central-Texas elementary schools. Of the 480 students in the 24 classrooms randomly assigned to either a seated or stand-biased desk equipped classroom, 374 agreed to participate in a week-long data collection during the fall and spring semesters. Each participant’s data was collected using Sensewear® armb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(109 citation statements)
references
References 25 publications
3
103
0
3
Order By: Relevance
“…The study sample sizes ranged from 8 to 337 participants, and most were either a feasibility or pilot study, with the exception of 1 large RCT conducted in 3 elementary schools. 25 Participants' mean age varied across studies, from 8.0 to 11.6 years; the sample age was not reported in 1 study. 24 Gender was reported in all but 1 study, and the proportions of girls ranged from 37.5% to 58.3%.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The study sample sizes ranged from 8 to 337 participants, and most were either a feasibility or pilot study, with the exception of 1 large RCT conducted in 3 elementary schools. 25 Participants' mean age varied across studies, from 8.0 to 11.6 years; the sample age was not reported in 1 study. 24 Gender was reported in all but 1 study, and the proportions of girls ranged from 37.5% to 58.3%.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…interacting with the tablet PC, the motor tasks, and the use of the standing desk, could have focused the child's attention and this could have resulted in more accurate movements when standing This does seem plausible considering that although previous research has reported that while objective measurements showed no difference in 'focus' or attention of participants, all class teachers reported behavioural benefits associated with using standing desks in the classroom (3,24).…”
Section: Discussionmentioning
confidence: 59%
“…Together, this suggests that successful reduction of sedentary behaviour is important for both the primary and secondary prevention of a range of diseases. Recent attempts to reduce sedentary behaviour, and increase physical activity levels has included modifying the classroom or work environment to encourage standing behaviour, via the installation of standing desks, with initial promising results (3).…”
Section: Introductionmentioning
confidence: 99%
“…Use of the stability ball and the cushion promoted greater energy expended compared to the flat surface chair by 10.4%, (p=0.01) and 9.6% (p=0.03), respectively, indicating that the yielding surface may be an effective means to forcing muscle to contract. In addition, studies of standing desk question their value specific to energy expenditure as small increases or no statistically significant change has been reported in children (Benden, Zhao, Jeffrey, Wendel, & Blake, 2014) and adults (Reiff, Marlatt, & Dengel, 2012;Speck and Schmitz, 2011). Nonetheless, Benden et al (2014) and Reiff et al (2012) explained the practicality of implementing the standing desks into classrooms.…”
Section: Worktationsmentioning
confidence: 99%
“…In addition, studies of standing desk question their value specific to energy expenditure as small increases or no statistically significant change has been reported in children (Benden, Zhao, Jeffrey, Wendel, & Blake, 2014) and adults (Reiff, Marlatt, & Dengel, 2012;Speck and Schmitz, 2011). Nonetheless, Benden et al (2014) and Reiff et al (2012) explained the practicality of implementing the standing desks into classrooms. Despite relatively small increases in energy expenditure, the modest activity of standing by children and collegeage students may be beneficial in the long term due to the accumulation effect over a lifetime.…”
Section: Worktationsmentioning
confidence: 99%